MY SAY: Reprioritising innovation - Abd Razak, Dzulkifli (2010)
In a May 30 interview on a weekly public affairs show hosted by journalist and author Fareed Zakaria on CNN, Microsoft Corp chairman Bill Gates mentioned the need "to reorder the priorities of the innovation system" in making changes in the health care sector. The fact that "the priorities of the innovation system" can be reordered implies that there can be more than one innovation system, and that not all innovation systems work wonders.